The Ependymal Region Prevents Glioblastoma From Penetrating Into the Ventricle via a Nonmechanical Force - Li, Kaishu; Song, Haimin; Wang, Chaohu; Lin, Zhiying; Yi, Guozhong; Yang, Runwei; Ni, Bowen; Wang, Ziyu; Zhu, Taichen; Zhang, Wanghao; Wang, Xiran; Liu, Zhifeng; et al. (Frontiers in Neuroanatomy, 2021)
BACKGROUND: Intraventricular penetration is rare in glioblastoma (GBM). Whether the ependymal region including the ependyma and subventricular zone (SVZ) can prevent GBM invasion remains unclear. METHODS: Magnetic resonance imaging (MRI) and haematoxylin–eosin (HE) staining were performed to evaluate the size and anatomical locations of GBM. Binary logistic regression analysis was used to assess the correlation between tumour-ependyma contact, ventricle penetration and clinical characteristics. Cell migration and invasion were assessed via Transwell assays and an orthotopic transplantation model. RESULTS: Among 357 patients with GBM, the majority (66 %) showed ependymal region contact, and 34 patients (10 %) showed ventricle penetration of GBM. GBM cells were spread along the ependyma in the orthotopic transplantation model. The longest tumour diameter was an independent risk factor for GBM-ependymal region contact, as demonstrated by univariate (OR = 1.706, p < 0.0001) and multivariate logistic regression analyses (OR = 1.767, p < 0.0001), but was not associated with ventricle penetration. Cerebrospinal fluid (CSF) could significantly induce tumour cell migration (p < 0.0001), and GBM could grow in CSF. Compared with those from the cortex, cells from the ependymal region attenuated the invasion of C6 whether cocultured with C6 or mixed with Matrigel (p = 0.0054 and p = 0.0488). Immunofluorescence analysis shows a thin gap with GFAP expression delimiting the tumour and ependymal region. CONCLUSION: The ependymal region might restrict GBM cells from entering the ventricle via a nonmechanical force. Further studies in this area may reveal mechanisms that occur in GBM patients and may enable the design of new therapeutic strategies.